The New Grove guide to Wagner and his operas - Millington, Barry (New Grove composers series., 2006)
One of the most controversial figures in the history of ideas as well as music, Richard Wagner continues to stimulate debate whenever his works are performed. Drawing upon the scholarship of The New Grove Dictionary of Opera, the most comprehensive dictionary of opera in the world, Barry Millington offers a concise, portable survey and guide, which will make a welcome addition to the shelf of anyone who loves opera. Millington has completely updated the original pieces and contributed four new chapters on Wagner, including a summary of Wagner productions from 1876 to the present day, a suggested listening and viewing gyide, complete chronology of Wagner's operas, and a glossary of terms that will delight any opera-goer. In addition, there are detailed entries on each of Wagner's operas, a main biographical section, and a group of separate articles on such topics as Leitmotif and Gesamtkunstwerk, as well as a newly revised updated article on Bayreuth. Complete with a new preface, updated bibliography, glossary, and discography--including first release dates of each recording--The New Grove Guide to Wagner and his Operas furnishes both seasoned Wagner-lovers and neophytes with all they require for an in-depth appreciation of this unique historical figure.